2022
DOI: 10.1063/5.0058170
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of functional properties of V0.6Ti0.4 alloy superconductor by the addition of yttrium

Abstract: We show here that yttrium is immiscible and precipitates with various sizes in the body centered cubic V0.6Ti0.4 alloy superconductor. The number and size of the precipitates are found to depend on the amount of yttrium added. Precipitates with various sizes up to 30 μm are found in the V0.6Ti0.4 alloy containing 5 at. % yttrium. The large amount of line disorders generated by the addition of yttrium in this alloy is found to be effective in pinning the magnetic flux lines. While the superconducting transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Detailed microscopy studies on Y0 and Y1-Y5 alloys can be found elsewhere [8,22,25]. Here, we highlight some important points required for the present study.…”
Section: Microscopic Featuresmentioning
confidence: 86%
See 4 more Smart Citations
“…Detailed microscopy studies on Y0 and Y1-Y5 alloys can be found elsewhere [8,22,25]. Here, we highlight some important points required for the present study.…”
Section: Microscopic Featuresmentioning
confidence: 86%
“…Our previous studies show that inhomogeneous flux pinning together with significant flux creep are the reasons behind the HFPME in V-Ti alloys [7], and that the absence of this phenomenon in V 0.6 Ti 0.4 is due to its low flux creep [7]. Recently, we have shown that the rare earths (RE) are immiscible in the V 0.6 Ti 0.4 phase and precipitate along the grain boundaries [21,22]. We also observed that the distribution of the size of precipitates depends on the amount of RE element present in the alloy [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations